The Effectiveness of Kids Athletics Games as Motion Stimulation for Elementary School Children: a Literature Review - Anisah, Dakwatul; Kamidi, Amrozi; Tuasikal, Abdul Rachman Syam; Suroto, Suroto (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The purpose of this review is to find out the effectiveness of kids athletics game as a stimulation of elementary school children. The method used is a journal search system on Google with the keyword kids’ athletic games on children’s movements. Journals are used as literature with full text inclusion criteria, the subjects are elementary school children, type of journals are journals of the last 6 years. The results of the review showed that kids’ athletics games can improve motion in elementary school children. The conclusion in this journal review is an effective kids’ athletics game as a stimulation of elementary school children’s movements